UJI PENGOLAHAN CRUDE OIL CONTAMINATED SOIL DENGAN UREA DAN TSP UNTUK PENURUNAN TPH (Jurnal Pilar Sains, 2007)
A research of crude oil contaminated soil (COCS) by addition urea and TSP for decreasing Total PetroleumHydrocarbon (TPH). The research consist of three steps (1) Biodegradability assessment (2) BioavailabillityAssessment (3) Prelimanary Confirmation.The result showed that TPH of COCS was able to decrease until 3.722% with using 35 g Urea/14 kgCOCS. Added liquid urea better than solid urea.Key Words: COCS, Total Petroleum Hydrocarbon